El redescubrimiento de la imaginación en el occidente moderno - Beas, Carlos (1983)
When we could thlnk that there was a total victory of the "technological intelligence", the recognition of imaginatlon comes in a sort of pendular movement. Devaluated as an lnstrument of knowledge by the positivist modern attitude, lmagination has continued to influence all levels of human life. Those sclences that strlve toward an integral knowledge of the human being have to deal with the reallty of imagination.